THE LITERARY WORKS OF LEO TOLSTOY AND OSCAR WILDE AS FASHION INSPIRATION (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
The phenomenon of fashion, clothing, and dress is complex. This phenomenon is viewed from the perspectives of sociology, history, anthropology, and costume design. It is no coincidence that there is a saying, “A suit doesn't cost a man, but it says a lot about him.” Culture and the changes it brings are often woven into clothing. In this paper, two models of clothing inspired by famous world classics are developed. The design of both models shows the inextricable link between literature and fashion design, demonstrating how design subtly enriches and vividly reflects the writer's imagination.
Keywords: literature; fashion; classics; design.